(untitled) (JURNAL ADMINISTRASI PUBLIK, 2016)
Abstract: this study aims to facilitate any work that was conducted in Ministry effectiveness see how retirement payment of civil servant in PT Taspen Manado Branch. Based on the results of the study Branch PT Taspen Manado need to increase retirement payment service so that there is no delay in payment of retirement services. Research methods in this study is a qualitative research method, and data collectiontechniques in the study of observation/observation directly to the location of research, conduct interviews, and documentation. The results showed there is still a delay in the payment of pensions of the Ministry civil servant in PT Taspen. branch of Manado. So there is no delay in payment of the pension service in influence by the performance, each of the fields that exist in the Office Branch Taspen Manado. Keywords: Effectiveness Of Service, Payment Of The Pension